Feasibility of preparing functionalize Y2O3 ceramic membrane with fluorinated polymers via UV photopolymerization for vapor transport application - Nur Zhatul Shima Yahaya; Intan Nuralisa Mad Dali; Noor Fadilah Yusof; Mohamad Zahir Mohamad Pauzi; Amirul Afiat Raffi; Norfazliana Abdullah; Khairul Hamimah Abas; Mohd Hafiz Dzarfan Othman; Juhana Jaafar; Mukhlis Abdul Rahman (Elsevier Ltd., 2025)
Functionalization through hydrophobic group incorporation has been widely acknowledged for preparation of advanced ceramic membrane. However, current popular method such as silane grafting was still complicated, produced unstable coating and high possibility of leaching into the environment. Hence, this work presented an alternative functionalization via UV photopolymerization where the process is facile and employed readily available fluorinated polymers; polyvinylidene fluoride (PVDF) and UV curable resin (UCR). Tuning the oxygen vacancy defect by inserting F- ion into O2− ion position in the metal oxide structure improved the membrane overall properties by forming a uniform, smooth, thin layer and well-coated active layer as shown by sample Y-1450-U-LOW. In comparison to silane grafting, the polymer coating layer in this study is chemically bonded to the metal oxide structure where it forms a strong and stabilized composite layer membrane consisting of Y-F bond at the interface. The success of this functionalization is further proven by the high membrane distillation performance as the NaCl rejection increased from 30.70 % to 99.99 % with permeate flux value of 5.66 L/m2.h. Adjustment in the feed NaCl temperature from 25 °C to 60 °C created more pathway for vapor transport, allowing the best membrane (Y-1450-U-LOW) to reach highest permeate flux value (29.40 L/m2∙h) so far in the literature. The stabilized active layer consists of the Y-F bond further sustaining the NaCl rejection at 99 %.